A prospective analysis of circulating saturated and monounsaturated fatty acids and risk of non‐Hodgkin lymphoma. Issue 8 (10th August 2018) - Chiu, Yu‐Han; Bertrand, Kimberly A.; Zhang, Shumin; Laden, Francine; Epstein, Mara M.; Rosner, Bernard A.; Chiuve, Stephanie; Campos, Hannia; Giovannucci, Edward L.; Chavarro, Jorge E.; Birmann, Brenda M.
Abstract : Circulating saturated (SFA) and monounsaturated fatty acids (MUFA), which are predominantly derived from endogenous metabolism, may influence non‐Hodgkin lymphoma (NHL) risk by modulating inflammation or lymphocyte membrane stability. However, few biomarker studies have evaluated NHL risk associated with these fats. We conducted a prospective study of 583 incident NHL cases and 583 individually matched controls with archived pre‐diagnosis red blood cell (RBC) specimens in the Nurses' Health Study (NHS) and Health Professionals Follow‐Up Study (HPFS). RBC membrane fatty acid levels were measured using gas chromatography. Using multivariable logistic regression, we estimated odds ratios (OR) and 95% confidence intervals (CI) for risk of NHL and major NHL subtypes including T cell NHL (T‐NHL), B cell NHL (B‐NHL) and three individual B‐NHLs: chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL), diffuse large B‐cell lymphoma (DLBCL) and follicular lymphoma. RBC SFA and MUFA levels were not associated with NHL risk overall. However, RBC very long chain SFA levels (VLCSFA; 20:0, 22:0, 23:0) were inversely associated with B‐NHLs other than CLL/SLL; ORs (95% CIs) per standard deviation (SD) increase in level were 0.81 (0.70, 0.95) for 20:0, 0.82 (0.70, 0.95) for 22:0 and 0.82 (0.70, 0.96) for 23:0 VLCSFA. Also, both VLCSFA and MUFA levels were inversely associated with T‐NHL [ORs (95% CIs) per SD: VLCSFA, 0.63 (0.40, 0.99); MUFA, 0.63 (0.40, 0.99)]. The findings of inverse associations for VLCSFAs with B‐NHLs other than CLL/SLL and for VLCSFA and MUFA with T‐NHL suggest an influence of fatty acid metabolism on lymphomagenesis. Abstract : What's new? Erythrocyte fatty acids are reliable biomarkers of dietary fat intake and endogenous lipogenesis and are known to be associated with certain diseases. In the present nested case‐control study, these fatty acids were investigated for their potential association with risk of non‐Hodgkin lymphoma (NHL). For overall NHL risk, no association was detected with saturated or monounsaturated fatty acid (MUFA) levels. By comparison, very‐long‐chain saturated fatty acids (VLCSFA) were inversely associated with risks of some types of B‐cell NHL, and both VLCSFA and MUFA levels were inversely associated with T‐cell NHL. The findings suggest that endogenous fatty acids or their generation potentially influence lymphomagenesis.